Review of Imágenes humanísticas para una sociedad educativa - Cayetano Espejo Marín (Investigaciones Geográficas)
Nineteen lecturers from the Faculty of Education and Humanities Sciences of Cuenca (University of Castilla-La Mancha) have published a book on various areas related to social education and humanities. Each chapter is devoted to aspects that deal with the development of their subject programmes. The book offers a variety of human science topics that expands our understanding through images of geographic, artistic, historic, psychological, economic, and educational realities.